2000
DOI: 10.1002/cjce.5450780418
|View full text |Cite
|
Sign up to set email alerts
|

Predicting pressure gradients in heavy oil—water pipelines

Abstract: Experimental investigations of the flow of water‐heavy oil mixtures at velocities typical of oil‐field gathering systems show that continuous water assisted flow at very low pressure gradients can be achieved. The principal criterion to be satisfied in establishing this desirable flow regime appears to be use of sufficient water, with the velocity also playing a role. It also appears that oil viscosity and water fraction effects on pressure gradient are small provided the beneficial flow regime is established.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
96
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(105 citation statements)
references
References 4 publications
9
96
0
Order By: Relevance
“…The very low pressure gradients showed that the second regime must also be different from stratified flow. The second regime occurred at higher velocities (typically above 0.1 m/s) and are discussed elsewhere (McKibben et al, 2000) in connection with flow in pipeline gathering systems. There was no visual evidence of a lubricating water layer at the pipe wall in either regime.…”
Section: Continuous Injectionmentioning
confidence: 98%
“…The very low pressure gradients showed that the second regime must also be different from stratified flow. The second regime occurred at higher velocities (typically above 0.1 m/s) and are discussed elsewhere (McKibben et al, 2000) in connection with flow in pipeline gathering systems. There was no visual evidence of a lubricating water layer at the pipe wall in either regime.…”
Section: Continuous Injectionmentioning
confidence: 98%
“…This is because the relative velocity of this layer is negligible compared to the average mixture velocity (Joseph et al 1999;McKibben et al 2000McKibben et al , 2016Shook et al 2002;Schaan et al 2002;Vuong et al 2009). This wall coating layer can produce a large equivalent hydrodynamic roughness value: The typical equivalent roughness of a commercial steel pipe is about 0.045 mm, while the hydrodynamic roughness (inferred from pressure loss measurements) of a pipeline with a viscous oil layer on the pipe wall can be greater than 1 mm (Brauer 1963;Shook et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…These oil reserves are asphaltic, dense, and highly viscous, with bitumen being more dense and viscous than heavy oil (Saniere et al 2004). Densities of these oils are nearly the same as that of water, whereas their viscosities are higher than that of water by orders of magnitude (McKibben et al 2000). Therefore, the production of these non-conventional oils requires extraordinary techniques that are not needed to recover traditional petroleum deposits.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations